2019
DOI: 10.1186/s13613-019-0560-5
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of airflows by electrical impedance tomography in intubated hypoxemic patients: an exploratory study

Abstract: Background Noninvasive monitoring of maximal inspiratory and expiratory flows (MIF and MEF, respectively) by electrical impedance tomography (EIT) might enable early recognition of changes in the mechanical properties of the respiratory system due to new conditions or in response to treatments. We aimed to validate EIT-based measures of MIF and MEF against spirometry in intubated hypoxemic patients during controlled ventilation and spontaneous breathing. Moreover, regional distribution of maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
6
1
Order By: Relevance
“…In two recently published studies in intubated patients, PTIF varied from 25–65 L/min [ 20 ] to 40–80 L/min [ 21 ], values that were higher than PTIF in our patients. This might be explained by the need to overcome the resistance of an endotracheal tube.…”
Section: Discussioncontrasting
confidence: 57%
“…In two recently published studies in intubated patients, PTIF varied from 25–65 L/min [ 20 ] to 40–80 L/min [ 21 ], values that were higher than PTIF in our patients. This might be explained by the need to overcome the resistance of an endotracheal tube.…”
Section: Discussioncontrasting
confidence: 57%
“…Still, EIT comes with reoccurring limitations, such as regional mechanics using RPF-based regional relative impedance data instead of absolute flows as measured by the ventilator. Regional impedances and regional volumes are different physical concepts, but Mauri et al described high correlations between EIT-derived peak flow and spirometry-based peak flow, meaning that the RPF approach is physiologically valid in terms of using air flow for determining regional lung mechanic parameters ( 30 ). Also, impedance changes occurring distally from the electrode band to a lesser extent contribute to the generation of EIT images which may lead to the over- or underestimation of regional airflow at the plane of the electrode band ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…When transitioning to spontaneous ventilation, EIT demonstrated that higher PEEP combined with lower pressure support smoothly redistributes V t from nondependent to dependent areas, improving the partial pressure of oxygen/fraction of inspired oxygen ratio and potentially diminishing focal stress (105, 106). Higher ΔP led to greater heterogeneity and basal collapse.…”
Section: Evaluating Patient-ventilator Interactions and Respiratory E...mentioning
confidence: 99%